Análisis de la gestión administrativa del Departamento de Recursos Humanos en la Empresa Imelda Banana S.A. - Barrera Salazar, Derian Gonzalo (2021)
This case study specifies the problems that exist in the company Imelda Banana SA, within the administrative process of the human resources department, where a set of studies and analysis of the behavior of all the personnel operating in the organization is carried out. Has predicted that the institution should take preventive actions promoting preventive projects, to obtain stability between employees and employers, and reduce the degree of conflicts that may develop due to dissatisfaction and demotivation that directly affect the performance of each employee, non-compliance with the rules, regulations and policies in force available to date within the operating sector of the company. Therefore, in recent years Imelda Banana s.a., has managed to expand, which has taken pains to develop qualities and skills despite all the difficulties that arise in the administrative management process in the human resources department, therefore it means that In the whole process carried out, not everything has been unfavorable, this has allowed this company that is dedicated to the production and export of bananas to remain in the market as a competitive company